2012
DOI: 10.1016/s0924-9338(12)74238-4
|View full text |Cite
|
Sign up to set email alerts
|

P-71 - Comparisnal investigation of emotional intelligent and tendency to addiction between addicted and nonaddicted people

Abstract: Positive influence of emotional intelligence (EI) on psychological functions is fast growing in many aspects of social life and higher levels of emotional intelligence can be important in human's behavior. So this study investigated emotional intelligence in addicted and nonaddicted people. Method: In sampling process a total of 73 addicted people and 73 non-addicted people were randomly selected. All participants were requested to complete Schutte´s Self-Report E / I Test (SSREIT). Results: Findings indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The study by Nadalinezhad et al showed that EI training reduced the illicit drug use potential in the youth (5). Various studies on students (9), addicts 2…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Nadalinezhad et al showed that EI training reduced the illicit drug use potential in the youth (5). Various studies on students (9), addicts 2…”
Section: Discussionmentioning
confidence: 99%
“…Several studies examined the relationship between EI and addiction (4,5). But, so far, the relationship between EI and the illicit drug use potential among nurses is not studied using an interventional method.…”
Section: Introductionmentioning
confidence: 99%